The effects of shocks, gender and culture on asset accumulation - Quisumbing, Agnes; Kumar, Neha; Berhman, Julia A. (United States Agency for International Development (USAID), 2012)
Sustainability poverty reduction is difficult to achieve without mechanisms that help households manage shocks. Covariate shocks, which impact virtually everyone in a community occur because of natural disasters, war, price instability and financial crises. Idiosyncratic shocks, which impact only individuals or specific households, commonly arise due to farm-specific crop failure or livestock mortality, illness, injury or death of a household member, or property loss due to fire or theft. Such shocks of the severely affect a household’s asset holdings thereby trapping a house-hold in chronic poverty